AB1134 Efficacy and safety of therapy by etanercept in combination with methotrexate for patients with juvenile idiopathic arthritis. (23rd January 2014) - Alexeeva, E.; Valiyeva, S.; Bzarova, T.; Isayeva, K.; Denisova, R.; Sleptsova, T.; Mitenko, E.; Tsurikova, N.; Chomakhidze, A.; Fetisova, A.
Abstract : Background: Juvenile idiopathic arthritis (JIA) - a chronic disease that leads to early disability of patients. Treatment of JIA is one of the most complex and urgent problems of rheumatology. The opportunity to achieve sustained remission with conventional antirheumatic drugs remains unlikely for many patients. However, the use of new expensive drugs for the treatment of JIA, biological agents, can achieve prolonged remission of the disease and improves prognosis. Objectives: Evaluate the efficacy and safety of etanercept therapy in combination with methotrexate in patients with JIA. Methods: Have been examined 25 patients aged 8 (6, 11) years old: 8 boys and 17 girls. 17 of them - with polyarthritis, 8 – with oligoarthritis. Etanercept was administered subcutaneously twice per week at a dose of 0.4 mg/kg of body weight (maximum 25 mg) for patients receiving methotrexate at a dose of 15 mg/m 2 per week. The treatment was during 48 weeks. The drug was canceled for 3 patients due to inefficiencies in terms of: 5 Weeks, 5 and 6 months. The effectiveness of therapy was evaluated according to criteria of the American College of Rheumatology (ACR Pedi-) - 30, 50, 70% improvement. Results: After 1 month of etanercept treatment by ACR pediatric criteria, 30% improvement was achieved in 72% of patients, 50% -in 40% of patients and 70% - in 12% of patients. After 6 months of treatment the improvement remained in 90% of children by the ACR50 criterion, and ACR70 criterion have been registered in 59%. After 48 weeks of etanercept therapy, the improvement of 50 and 70% have been registered in 100 and 86% of patients respectively. After 6 months of treatment status of inactive disease was reported in 59% of patients and after 12 months – in 86% of patients. Adverse events were mild or medium-heavy (3) and did not require discontinuation of the drug, acute bronchitis, exacerbation of herpetic infection (1), rinitis (1), pain at the injection site (1). Conclusions: Etanercept is highly effective and safe for patients with oligo and polyarthritis, it causes the development of remission after a year of therapy in 86% of patients. Disclosure of Interest: None Declared